Решаем дискриминант:
-x^2-2x+5=0
D=b²-4ac=> (-2)²-4*(-1)*5 = 4+20 = 24
x =
x₁ =
x₂ =
Получаем:
Объяснение:
трррррррррррррррррррррррррррр
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Решаем дискриминант:
-x^2-2x+5=0
D=b²-4ac=> (-2)²-4*(-1)*5 = 4+20 = 24
x =![\frac{-b+-\sqrt{D} }{2a} \frac{-b+-\sqrt{D} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%7BD%7D%20%7D%7B2a%7D)
x₁ =![\frac{2+24}{-2} = -13 \frac{2+24}{-2} = -13](https://tex.z-dn.net/?f=%5Cfrac%7B2%2B24%7D%7B-2%7D%20%3D%20-13)
x₂ =![\frac{2-24}{-2} = -11 \frac{2-24}{-2} = -11](https://tex.z-dn.net/?f=%5Cfrac%7B2-24%7D%7B-2%7D%20%3D%20-11)
Получаем:![\frac{(x+13)(x+11)}{x^2-25} \frac{(x+13)(x+11)}{x^2-25}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2B13%29%28x%2B11%29%7D%7Bx%5E2-25%7D)
Объяснение:
трррррррррррррррррррррррррррр